Monoclonal Antibodies in Neurology: Current State and Future Development - Zakharova, M. N. (Human physiology, 2022)
Monoclonal antibodies are one of the fastest growing areas of specific therapy for cancer, infectious, autoimmune, and demyelinating diseases. The main targets of monoclonal antibodies in autoimmune and demyelinating diseases are T and B lymphocytes, cytokines, complement, and adhesion molecules. In the field of neurodegenerative diseases, the largest number of studies has been carried out in patients with Alzheimer’s disease, in which the target for monoclonal antibodies is pathologically altered beta-amyloid protein that accumulates in the brain parenchyma. This review presents new therapeutic approaches to the use of antibody fragments, with an emphasis on their new class, nanobodies. Special attention is paid to new anti-CD20 and anti-CD19 monoclonal antibody drugs in multiple sclerosis (ocrelizumab, ofatumumab) and neuromyelitis optica (inebilizumab). Ocrelizumab is the first medication that proved to be effective in primary progressive multiple sclerosis. There have been significant advances in the treatment of neuromyelitis optica: the first multicenter study of Inebilizumab (MEDI-551) is currently underway.